Low energy phonon excitations in relaxor ferroelectric (1-x)Pb(Zn1/3Nb2/3)O3-xPbTiO3 - D. Wongratanaphisan (2018)
Neutron measurements of the low energy phonons in relaxor ferroelectric (1-x) Pb(Zn 1/3 Nb 2/3 )O 3 -xPbTiO 3 (x = 0-15%) show lattice dynamic connecting to diffuse scattering. In (200) zone, where there is no observable diffuse scattering, the effect of the diffuse on phonons is expected to be minimal. A comparison of the scattering in this zone to that in (110), where significant diffuse is present, reveals strong coupling of the diffuse component to the acoustic mode. We speculate that coupling to central peak is the reason for aiding interpretation and analysis of the lattice dynamics based on data from zones with a strong diffuse component. Copyright © Taylor & Francis Group, LLC.